Traditions of Russian Tableful: Verbs, Denoting Ritualized Bacchic Actions - O. A. Dimitrieva (Научный диалог)
The article is devoted to the study of verbs denoting ritualized Bacchic actions. The author continues a series of works devoted to the study of Bacchic action in a broad sense in relation to the national picture of the world and mentality. Verbs obmyt’ and sprysnut’ meaning ‘to celebrate any event’, their compatibility are considered, and also frequency of forms is analyzed. Thus, the most frequent form of the designated verbs is the infinitive in combination with the modal-characterizing word nado . The prescriptiveness of the action, its expectation by community is represented in the introductory constructions kak voditsya , po russkoy traditsii , soglasno vekovym traditsiyam , etc. According to the author, use of verbal nouns obmyv , sprysk shows that the actions-rituals are interpreted as “entities” outside of time and space. Attention is paid to the ritual Church verb prichastitsya . The transition of the verb from the sacred to the profane sphere is noted, which is linked with the change of the axiological component. The profanical interpretation of the action, denoted by the verb prichastitsya , becomes possible with the expansion of its valence properties (in combination with a noun in the instrumental case - prichastitsya russkoy vodochkoy ). The material for the study was the examples of modern artistic and journalistic texts extracted from The National Corpus of the Russian Language.